The Effectiveness of Peer-Mediated Lego-Based Intervention to Improve the Social Skills of Primary School Students with ASD - Vijaendren, Daashwinni; Jamaludin, Anne Noor Sri Juwaneeta (Jurnal Pendidikan Bitara UPSI, 2025)
Peer-mediated LEGO-based interventions have been a promising intervention to enhance the social skills of primary school students with ASD. This study examines the effectiveness of peer-mediated LEGO-based intervention in improving the social skills of primary school students in an integrated government school, looking into the findings, challenges, and recommendations. This LEGO-based intervention is a structured activity focusing on social initiations and responses. A total of 30 students, 10 students with ASD and 20 typically developing students, participated in a seven-week intervention that psychology students facilitated. These students were organized into ten groups, each consisting of two typically developing children and one child diagnosed with ASD. The findings showed a significant improvement in social skills regarding social responses and social initiations from the third week onwards. In addition, there was a slight decrease in the peer prompts by typically developing children post-intervention, which indicates that there are great opportunities for individuals with ASD to develop their independence. However, there are challenges faced during the intervention, which include limited resources, an unconducive environment, and time constraints. Regardless of the challenges, the findings showed a significant increase in social skills among primary school students with ASD. The results have implications that notify important authorities, such as educators and practitioners, to advocate for having a structured social skill intervention accommodated in government schools. Increasing the funds for necessary resources, such as intervention materials and teacher training, helps create an inclusive environment and support the social development of children with ASD.